Wuji Wan ameliorates ulcerative colitis by restoring impaired membrane transport - Zhang, Jianyu; Zhang, Yang; Guo, Yuxuan; Sun, Yi; Li, Yujie; Li, Qi; Chen, Ying; Wang, Yajie; Yang, Qing; Zhang, Meiyu; Weng, Xiaogang; Deng, Zhihao (Frontiers in Pharmacology, 2026)
IntroductionWuji Wan (WJW) is a classical Chinese formula traditionally prescribed for diarrhea/dysentery and abdominal pain. In ulcerative colitis (UC), inflammatory diarrhea reflects not only mucosal inflammation but also inflammation-linked disruption of epithelial electrolyte and water handling, highlighting membrane transport as a mechanistic bridge between symptom burden and immune activation. However, it remains unclear whether WJW confers therapeutic benefit in UC and whether any benefit is accompanied by coordinated regulation of membrane-transport–linked pathways. This study therefore asked whether WJW shows therapeutic effects in a UC model and whether these effects are accompanied by changes in epithelial Na+/Cl− transport and water-channel programs and by modulation of the T-cell–linked potassium channel Kv1.3.MethodsWe investigated this question in a mouse model of DSS-induced colitis (3% dextran sulfate sodium). Our assessment included disease activity index (DAI) scores, histopathological analysis, ELISA, Western blotting, untargeted metabolomics, and whole-cell patch-clamp electrophysiology.ResultsWJW significantly ameliorated DSS-induced colitis, as reflected by improved colonic pathology and partial normalization of DSS-associated serum metabolic perturbations. Untargeted metabolomics highlighted transport-related pathways. WJW increased/normalized the expression of key epithelial transport proteins involved in Na+/Cl− absorption and water handling, including sodium/hydrogen exchanger 3 (NHE3), epithelial sodium channel (ENaC), downregulated in adenoma (DRA), aquaporin-3 (AQP3), and aquaporin-8 (AQP8). In parallel, WJW reduced IL-6, IL-17A, and IFN-γ and dampened ERK/NF-κB pathway activation. WJW also reduced colonic Kv1.3 protein expression, and WJW-containing plasma directly inhibited Kv1.3 currents in Jurkat T cells.ConclusionWJW ameliorated DSS-induced colitis and was accompanied by coordinated modulation of epithelial and immune membrane-transport–linked readouts.